Pengaruh Kompetensi Profesional, Motivasi, Dan Iklim Kerja Terhadap Efektivitas Kerja Dosen di STIE Bina Karya Tebing Tinggi - Ernita Sibuea; Elfrianto Elfrianto; Emilda Sulasmi; Parulian Sibuea (EduTech: Jurnal Ilmu Pendidikan dan Ilmu Sosial, 2023)
The purpose of this study was to determine the effect of professional competence, motivation, and work climate on the work effectiveness of lecturers at STIE Bina Karya Tebing Tinggi. This research was conducted at STIE Bina Karya Tebing Tinggi with a total sample of 58 people. Data collection techniques using questionnaires and data analysis techniques, namely validity, reliability, t-tests, and F-tests, The results showed that there was an influence of professional competence on the effectiveness of lecturers' work, where a t-count value of 4.483 was obtained with a Sig value of 0.006 0.05, and the results of simple regression analysis show the regression equation = 27.096 +.709X1, which means that every increase of one professional competency value will be followed by an increase in the value of the lecturer's work effectiveness of 0.709. There is an influence of work motivation on the effectiveness of lecturer work, where the t value obtained is 36.066 with a Sig value of 0.000 0.05, and the results of simple regression analysis show the regression equation = 27,096 + 1,151 X2, which means that every increase of one value of motivation will be followed by an increase in lecturer work effectiveness of 1.151. There is an influence of the work climate on the effectiveness of the lecturer's work, where the t value obtained is 31.897 with the acquisition of a Sig value of 0.000 0.05, and the results of the simple regression analysis show the regression equation = 27,096 + 1,025 X3, which means that every increase of one work climate value will be followed by an increase in the effectiveness of the lecturer's work of 1,025. There is an influence of professional competence (X1), motivation (X2), and work climate (X3) together on the effectiveness of lecturer work, where the calculated F value is 42.581 and the significance (Sig.) is 0.000. The magnitude of the influence is shown by the coefficient of determination R2 (R square) = 0.959, which means that professional competence (X1), motivation (X2), and work climate (X3) together have an influence on lecturer work effectiveness by 95.9%, and the remaining 4.1% is determined by other factors. The results of simple regression analysis show the equation = 27.096 +.0.709 X1 + 1.151 X2 + 1.025 X3 + e.